Palm-based medium-and-long-chain triaclyglycerol (P-MLCT): production via enzymatic interesterification and optimization using response surface methodology (RSM) - Lee, Yee Ying; Tang, Teck Kim; Phuah, Eng Tong; Ab Karim, Nur Azwani; Mohd Alwi, Siti Maslina; Lai, Oi Ming (Springer, 2014)
Structured lipid such as medium-and long-chain triacylglycerol (MLCT) is claimed to be able to suppress body fat accumulation and be used to manage obesity. Response surface methodology (RSM) with four factors and three levels (+1,0,−1) faced centered composite design (FCCD) was employed for optimization of the enzymatic interesterification conditions of palm-based MLCT (P-MLCT) production. The effect of the four variables namely: substrate ratio palm kernel oil: palm oil, PKO:PO (40:60–100:0 w/w), temperature (50–70 °C), reaction time (0.5–7.5 h) and enzyme load (5–15 % w/w) on the P-MLCT yield (%) and by products (%) produced were investigated. The responses were determined via acylglycerol composition obtained from high performance liquid chromatography. Well-fitted models were successfully established for both responses: P-MLCT yield (R 2 = 0.9979) and by-products (R 2 = 0.9892). The P-MLCT yield was significantly (P < 0.05) affected by substrate ratio, reaction time and reaction temperature but not enzyme load (P > 0.05). Substrate ratio PKO: PO (100:0 w/w) gave the highest yield of P-MLCT (61 %). Nonetheless, substrate ratio of PKO: PO (90:10w/w) was chosen to improve the fatty acid composition of the P-MLCT. The optimized conditions for substrate ratio PKO: PO (90:10 w/w) was 7.26 h, 50 °C and 5 % (w/w) Lipozyme TLIM lipase, which managed to give 60 % yields of P-MLCT. Up scaled results in stirred tank batch reactor gave similar yields as lab scale. A 20 % increase in P-MLCT yield was obtained via RSM. The effect of enzymatic interesterification on the physicochemical properties of PKO:PO (90:10 w/w) were also studied. Thermoprofile showed that the P-MLCT oil melted below body temperature of 37 °C.